Prognostic and Clinicopathological Value of Programmed Cell Death Ligand1 Expression in Patients With Small Cell Lung Cancer: A Meta-Analysis - Cai, Huarong; Zhang, Haimei; Jiang, Yuequan (Frontiers in Oncology, 2020)
Background: Programmed death-ligand 1 (PD-L1) is an immune checkpoint molecule expressed by cancer cells. Previous studies have demonstrated the prognostic role of PD-L1 expression in patients with small cell lung cancer (SCLC), where the results were inconsistent. Therefore, we conducted a meta-analysis to identify the prognostic impact of PD-L1 on SCLC. Methods: We searched the PubMed, Embase, ISI Web of Science, and Cochrane Library databases for articles published before and on March 2nd, 2020. Data of PD-L1 expression in tumor cells detected using immunohistochemistry methods were extracted for analysis. Pooled hazard ratios (HRs) with confidence intervals (CIs) and odds ratios (ORs) with 95% CIs were calculated to assess the correlations among PD-L1, overall survival (OS), and clinicopathological factors. Results: Nine studies of 921 patients published between 2015 and 2019 were included in this meta-analysis. The pooled data (HR=0.91, 95% CI=0.46–1.80, p=0.787) indicated that PD-L1 expression is not a significant predictor of poor OS. Moreover, the results also revealed that PD-L1 expression is not significantly associated with gender (OR=1.12, 95% CI=0.73–1.74, p=0.601), age (OR=1.15, 95% CI=0.58–2.30, p=0.683), pN stage (OR=0.65, 95% CI=0.24–1.72, p=0.381), pT stage (OR=1.16, 95% CI=0.26–5.23, p=0.847), serum lactate dehydrogenase level (OR=1.06, 95% CI=0.13–8.43, p=0.958), or performance status (OR=0.69, 95% CI=0.24–1.95, p=0.479). No significant publication bias was detected in this meta-analysis. Conclusions: This meta-analysis suggests that PD-L1 expression is not a significant prognostic factor of poor survival in SCLC. Because of significant variations, high-quality studies are needed to validate our results.